2016
DOI: 10.18632/oncotarget.7431
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression is associated with epithelial-mesenchymal transition in head and neck squamous cell carcinoma

Abstract: Virus-associated malignancies and sarcomatoid cancers correlate with high PD-L1 expression, however, underlying mechanisms remain controversial. We evaluated the correlation between PD-L1 expression and epithelial-mesenchymal transition (EMT) in head and neck squamous cell carcinomas (HNSCC). Tumor tissues from 50 patients with HNSCC were evaluated for PD-L1 by immunohistochemistry, which showed 32 (64.0%) were PD-L1 positive (PD-L1+). Interestingly, PD-L1 expression was significantly associated with EMT (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
131
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 54 publications
8
131
0
1
Order By: Relevance
“…The differences observed in the positivity rate of PD-L1 in ESCC may be attributed to the antibodies used in the IHC staining and the scoring criteria for the staining. The positivity rate of PD-L1 is also dependent on whether the patients received any treatment before sample collection since chemotherapy and radiotherapy induce PD-L1 expression, as demonstrated by our current study and other reports [8], [26], [27]. Previous studies demonstrate that high PD-L1 expression is associated with advanced disease and lymph node metastasis in various cancers [28], [29], [30].…”
Section: Discussionsupporting
confidence: 80%
“…The differences observed in the positivity rate of PD-L1 in ESCC may be attributed to the antibodies used in the IHC staining and the scoring criteria for the staining. The positivity rate of PD-L1 is also dependent on whether the patients received any treatment before sample collection since chemotherapy and radiotherapy induce PD-L1 expression, as demonstrated by our current study and other reports [8], [26], [27]. Previous studies demonstrate that high PD-L1 expression is associated with advanced disease and lymph node metastasis in various cancers [28], [29], [30].…”
Section: Discussionsupporting
confidence: 80%
“…Many recent studies have highlighted the critical role of PD-L1 in regulating the biological functions of cancer cells themselves, including cell proliferation, migration, metastasis, chemo/radio-resistance, and the promotion of epithelial to mesenchymal transition [9,10,18,21,23,[30][31][32]. It has been suggested that signal pathways such as JAK/ STAT1/IRF-1, MEK/ERK/STAT1 and PKD2 etc.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was shown that PD-L1 expression could induce epithelial-to-mesenchymal transition in renal cell carcinoma by activating the transcription factor SREBP-1c [22]. Notably, the survival analysis in the TCGA database confirmed that prognoses were better for PD-L1 + /EMT -patients than for PD-L1 + /EMT + patients with human head and neck squamous cell carcinoma [23]. In our previously published studies, we have separately identified PD-L1 expression and EMT as important prognostic factors in human esophageal cancer [24,25].…”
Section: Introductionmentioning
confidence: 96%
“…For example, Hwu and colleagues have recently shown that tumor loss of PTEN in melanoma leads to increased inhibition of a T-cell mediated tumor response, with PI3 kinase inhibition at least partially reversing this phenomenon(13). Moreover, the epithelial to mesenchymal transition (EMT) has been linked to upregulation of immune checkpoints such as PD-L1(14,15). As EMT has been linked to both Axl and PI3 kinase activation as well as radiation resistance, it is possible that these signaling cascades may be driving both intrinsic radioresistance as well as inhibition of the tumor immune response necessary for radioresponse(1618)…”
Section: Introductionmentioning
confidence: 99%